(untitled) (Indonesian Tax Justice Review, 2025)
Tax treaties play a critical role in allocating taxing rights between countries, often constraining source-based taxation in developing economies. This paper compares tax treaty networks and withholding tax provisions in Indonesia, Thailand, and Malaysia. Using doctrinal treaty analysis, the study evaluates the distributive consequences of treaty design. The findings indicate that extensive treaty concessions significantly reduce source-country revenues. The paper argues that treaty policy choices have long-term implications for tax justice. The global contribution of this study lies in highlighting how treaty practices in ASEAN reflect broader structural inequities in international tax law. The study contributes to calls for treaty reform to better protect developing country interests.